(untitled) (Revista Venezolana de Salud Pública, 2018)
Pediculosis capitis is caused by Pediculus capitis, wingless insect that is specialized to live on the human scalp. This ectoparasitosis remains common today especially in children of school age and with socio sanitary deficiencies. The aim of this cross-sectional study, conducted in June 2014, was to determine the prevalence of head lice in people of the indigenous community “Itopoicon”, Bolívar State, Venezuela. After signing the informed consent, each participant filled a clinical epidemiological record and underwent an examination of the hair and scalp.